Multiple long-distance scrambling: Syntax as reflections of processing - Kempson, R; Kiaer, J (2010)
This paper argues that, with syntax defined as progressive projection of semantic representations along the left-to-right dimension provided by the sequence of words (Cann, Kempson and Marten 2005), explanations for local and (multiple) nonlocal scrambling of NPs in Japanese and Korean follow from general principles of tree growth, allowing differences between the languages while nevertheless retaining an integrated account of scrambling itself. This formalism is similar to the parsing mechanism of Miyamoto (2002), but goes further in using this as the base grammar formalism, with all concepts of movement replaced by progressive articulation of structural underspecification and tree growth starting from the left periphery. The account extends the analysis of Japanese scrambling of Cann et al. to encompass multiple long-distance scrambling, capturing both the attendant relative locality restriction on the constituents moved, and interaction of this restriction with scope-construal effects. Scope-construal variability is expressible as interaction between individual lexical specifications for the two languages and general constraints on scope construal; and the relative locality constraint on the construal of the expressions involved in multiple long-distance scrambling is an immediate consequence of the general dynamics of the framework. The resulting account extends Hawkins' (2004) program of defining grammars relative to performance considerations. Copyright © Cambridge University Press 2009.